Η δημιουργία μιας σειράς έργων τέχνης που εξερευνούν το φαινόμενο της αναγνώρισης ανύπαρκτων ή μη εξακριβωμένων μοτίβων - Παναγή, Μαρία (My University, 2025)
The aim of this research is to artistically explore the subject of random formations in nature (e.g., branches, trees, root systems) and the way they are perceived as patterns through the phenomenon of apophenia. The research began with a literature review of various scientific articles, accompanied by visual research in fields such as medicine, psychology, art, and botany, which align with the concept of apophenia. Regarding the methodology, the approach of arts-based research was followed. Initially, a bibliographic study was conducted to gather material that would support a deeper understanding of the components related to the research question. Following the literature review, the first stage involved visual research and a series of case studies. Subsequently, a series of artistic experiments were carried out, aiming to create drawings through various techniques. This process helped to conceptually clarify the artistic intention behind the research question and supported the analysis, interpretation, representation, and presentation of different ideas. After the initial experimental phase, observations were recorded, leading to a second cycle of artwork creation, this time with more specific goals. At this stage, elements such as randomness and the unconscious were also explored.
Keywords: Apophenia; Pareidolia; Symmetry and asymmetry; Printing methods; Αποφένια; Καλλιτεχνική έρευνα; Τυχαιότητα; Ασυνείδητο